Code-Switching in Contemporary Nigerian Hip Hop Songs - Oreoluwa, K.A. (University of Ghana, 2013)
Most Nigerian hip hop artistes use a combination of English and one or more local language(s) in writing the lyrics of their songs. Over the years, this has become a common trait in the hip hop world. English is the official language in Nigeria, therefore, the base language of most Nigerian hip hop songs is English even as they introduce local expressions into the lyrics. This process can be described as code-switching in songs. It is also to be noted that pidgin is also a local language in this context. This work examines the nature of code switching found in these songs and the possible reasons behind them. It also focuses on how the artistes code-switch. If we look at Nigerian hip hop songs, we will notice that code-switching here involves English and one (or more) of the three major languages in Nigeria, which are Yoruba, Hausa and Igbo. However, the constant use of Yoruba by the artistes cannot go unnoticed. Thus, Yoruba appears to be the most frequently used among the Nigerian languages and indeed, the titles of some songs attest to this. Pidgin in most Nigerian hip hop songs is also common. In Nigeria, pidgin cuts across the country making it easy for all Nigerians from different tribes and background to communicate with each other. Hence, most artistes use pidgin as well in their song lyrics.
Thesis (MA)-University of Ghana, 2013